Mechanical properties of hybrid thermosets from vinyl ester resin and acrylated epoxidized palm oil (AEPO) - Fakhari, Alireza (2015)
A series of green hybrid thermosetting resins composed of acrylated epoxidized palm oil (AEPO) and vinyl ester (VE) were prepared via free radical polymerization. The AEPO/VE ratio was varied between 5/95 and 20/80 wt.%. The mechanical properties of resulting hybrid systems were investigated by tensile and flexural tests. The results revealed that these hybrids exhibit mechanical properties comparable to those of commercial vinyl ester resins.